José Ingenieros and the Youthism The Critique to the League of Nations, 1923-1925 - Alexandra Pita González (Estudios de Teoría Literaria)
The present work reflects on the criticism that José Ingenieros made of the League of Nations through the response that he gave to a survey in 1923 and a speech he gave in Paris in 1925. The analysis of these two interventions refers us to his concept of the juvenilism, important and present in other texts of the author. The defense or juvenilism as a concept, but also as a representation not only of a sector of students but also of a new world here meritocracy should govern, is opposed to a Europe and its derivatives. The league of Nations will be understood from the European decadence from the anti-meritocratic and the corruption of ideals. The argument was used as an excuse to contrast the Geneva organization with the Latin American Union, but also to include itself in the debates of the civilizational crisis. Thus, the analysis of a conference and a survey allows us to understand, as textualities, the relationship between intentionality and historical consciousness from the perspective of intellectual networks.